(untitled) (Interdisciplinary Studies Journal, 2025)
This document presents a study on the impact of a multisensory teaching method on the visual processing of students with Dyslexic Learning Disorder, utilizing eye-tracking. The objective was to quantitatively and qualitatively evaluate changes in reading after the intervention. The methodology employed an applied and exploratory action-research approach, using partial data from a doctoral thesis titled "Eye Tracking And The Davis Multisensory Method: Cognitive Analysis In Teaching Students With Dyslexic Learning Disorder." The disclosed data pertains to a 5th-grade elementary school student from the city of Boa Vista-RR. A semi-structured interview, observation, and a Gazepoint GP3 HD eye-tracker were used to identify "trigger words" based on visual fixation time. The intervention included stages such as perceptual skill assessment, orientation procedures, fine-tuning, and mastery of basic symbols, with the tactile production of letters and words. The results indicated an improvement in reading speed and efficiency, with more fluid eye movement patterns and directed focus after applying the method. It is concluded that the multisensory teaching method is effective in reducing reading difficulties, validating its applicability in personalized diagnoses and interventions.